Membrane and synaptic properties of developing lateral geniculate nucleus neurons during retinogeniculate axon segregation. - White, C A (1992)
During the first postnatal month in the ferret (Mustela putorius furo), the projections from the retina to the lateral geniculate nucleus (LGN) become segregated into eye-specific layers and ON and OFF sublayers, a process that is thought to depend in part on neuronal activity. Remarkably, virtually nothing is known about the physiological features of LGN neurons during this period. We have recorded intracellularly from 46 A-layer neurons in slices of the ferret LGN between the ages of postnatal days 7 and 33. The passive membrane properties and current-voltage relationships of the developing neurons were similar in many, though not all, respects to those of adult LGN neurons. Action potentials in younger animals were smaller in amplitude and longer in duration than in older animals, but cells at all ages were capable of producing spike trains whose latency and spike number varied with stimulus intensity. In addition, cells at all ages responded with low-threshold potentials upon release from hyperpolarization. Slightly more than half of the LGN neurons responded to optic tract stimulation with excitatory postsynaptic potentials (EPSPs), inhibitory postsynaptic potentials (IPSPs), or EPSP-IPSP pairs, beginning with the youngest ages. Thus, as early as the second postnatal week, and much before the onset of pattern vision, LGN neurons have many of the membrane and synaptic properties of adult thalamic neurons. These data are consistent with LGN cells playing a significant role in activity-dependent reshaping of the retinogeniculate pathway.